HUBUNGAN PEMBERIAN PREMI PANEN KELAPA SAWIT DENGAN MOTIVASI KERJA KARYAWAN PANEN DI PT. NIAGAMAS GEMILANG KABUPATEN KUTAI KARTANEGARA PROVINSI KALIMANTAN TIMUR - Misnati Prihartini; Fadli Mulyadi; Rossy Mirasari (Politeknik Pertanian Negeri Samarinda, 2019)
Harvesting is important thing for oil palm company, because of that the company needs skilled harvesting employee. In order to achieve the company's goal thus the company needs to encourage employee by providing harvest premium to escalate employee's motivation. Therefore, this study aims to look for the correlation of giving harvest premium toward employee's work motivation. This study used quantitative description method with questioner and interview as method of collecting data. The subject of this study was 30 married harvesting employees. Based on the calculation result, researcher obtained the value of coefficient of correlation by 0,334 which mean the value of correlation (r) was between 0,20-0,399 which mean there was a weak correlation between premium variable (X) and motivation (Y). And the level of significance by 0,074 which was higher than the significance level of 0,05 thus could be concluded that provision of the harvest premium had a weak correlation toward employee work motivation and harvest premium had no significant effect on work motivation allegedly because the lack of fresh fruit bunches that ready to harvest in the field, field conditions and harvester productivity.